Outer Dynein Arm Light Chain 1 Is Essential for Controlling the Ciliary Response to Cyclic AMP in Paramecium tetraurelia - Kutomi, Osamu (American Society for Microbiology, 2012)
The individual role of the outer dynein arm light chains in the molecular mechanisms of ciliary movements in response to second messengers, such as Ca(2+) and cyclic nucleotides, is unclear. We examined the role of the gene termed the outer dynein arm light chain 1 (LC1) gene of Paramecium tetraurelia (ODAL1), a homologue of the outer dynein arm LC1 gene of Chlamydomonas reinhardtii, in ciliary movements by RNA interference (RNAi) using a feeding method. The ODAL1-silenced (ODAL1-RNAi) cells swam slowly, and their swimming velocity did not increase in response to membrane-hyperpolarizing stimuli. Ciliary movements on the cortical sheets of ODAL1-RNAi cells revealed that the ciliary beat frequency was significantly lower than that of control cells in the presence of ≥1 mM Mg(2+)-ATP. In addition, the ciliary orientation of ODAL1-RNAi cells did not change in response to cyclic AMP (cAMP). A 29-kDa protein phosphorylated in a cAMP-dependent manner in the control cells disappeared in the axoneme of ODAL1-RNAi cells. These results indicate that ODAL1 is essential for controlling the ciliary response by cAMP-dependent phosphorylation.